Chromium histidinate increases brain GLUT-1 and GLUT-3 levels impaired by insulin resistance - Komorowski, J.; Tuzcu, M.; Şahin, Nurhan.; Şahin, Kazım (Nature Publishing Group, 2009)
[Abstract Not Available]
24th International Symposium on Cerebral Blood Flow and Metabolism/9th International Conference on Quantification of Brain Function with PET -- JUN 29-JUL 03, 2009 -- Chicago, IL